METHODOLOGICAL PRINCIPLES OF PROFESSIONAL COMPETENCE DEVELOPMENT OF THE FUTURE BIOLOGY TEACHER - Rakhmatov Uchkun Ergashevich (International Scientific and Current Research Conferences, 2024)
The article discusses the methodical foundations of developing the professional competence of the future biology teacher. Including ways to improve them.